Composition and Impedance Heterogeneity in Oxide Electrode Cross‐Sections Detected by Raman Spectroscopy. Issue 9 (8th February 2018) - Gilbert, James A.; Maroni, Victor A.; Cui, Yanjie; Gosztola, David J.; Miller, Dean J.; Abraham, Daniel P.
Abstract: Lithium‐bearing layered transition metal oxides are the materials of choice for positive electrodes in high energy lithium‐ion cells being developed for electric vehicle applications. During electrochemical cycling, the loss of mobile lithium‐ions due to undesirable side reactions and an increase in cell resistance leads to a decline in the energy and power performance of the cells. This performance loss is often nonuniform across multiple cells, especially for those cycled at high voltages or high C‐rates. This nonuniformity results from inhomogeneous behavior in the battery electrodes, which can lead to localized areas that deteriorate faster than the neighboring regions. Raman spectroscopy is among the many techniques that are used to probe inhomogeneity in electrode behavior. Typically, Raman spectroscopy measurements on lithium‐ion cell electrodes are conducted in the top‐down mode, and at‐best produce an incomplete, surface biased account of electrode behavior. In contrast, micro‐Raman measurements conducted on ion‐milled electrode cross‐sections provide information from regions that span the full thickness of the electrode. Here, Raman spectroscopy data from pristine, aged, and relithiated/aged positive electrodes are reported. The spectral differences between oxide particles near the top‐surface and particles deeper into the aged electrodes clearly indicate compositional heterogeneities that arise during cell aging. Abstract : Mesoscale heterogeneities in layered‐oxide electrodes, which develop during electrochemical cycling, can significantly reduce the performance and life of lithium‐ion cells. Micro‐Raman spectroscopy can be used to study compositional heterogeneities across the electrode cross‐sections. These heterogeneities point to the evolution of high‐impedance areas, especially near the electrode–separator interface, in highly aged cells.